The sociocultural nature of writing in children with autism. (29th May 2022) - Maxwell, Jamie; Nelson, Ryan; Damico, Jack; Weill, Christine
Abstract : Background: In the field of communication disorders, practitioners work regularly with school-age children with autism. Routinely, socialization issues impact literacy in this population and consequently become areas of clinical concern. This study addressed common themes from an inquiry into the socialization processes of school-age children with autism as they engaged in writing events as a sociocultural tool in clinical contexts. Method: A qualitative methodology was employed to investigate how three students with autism used writing as a sociocultural tool, and what opportunities the writing activities created for socialization over the course of one semester in a group intervention setting. Results: Three general patterns emerged that highlight the strategies employed by participants which demonstrated their use of writing for socialization, and the sociocultural opportunities the writing process provided. Discussion/conclusion: This study demonstrated that the context of the writing events, where the sociocultural nature of writing was appreciated and valued, created unique opportunities for the participants to engage, socialize, and essentially create a local peer culture.